Hierarchia wartości cesarza Marka Aureliusza na podstawie jego "Rozmyślań" - Trzebuniak, Józef (Vox Patrum, 2013)
In this article a system of values of Mark Aurelius, the Roman emperor and the philosopher ruling in Rome in 161-188 years, was described. The hierarchy of these values is based on reflections of the „philosopher on the throne” included in his Meditations. In the first part a respect of the emperor was portrayed towards the visible world and the laws of nature which are ruling it. Next an importance of the virtue was emphasized in the view of the author of Meditations as well as how significant was the fulfilment of everyday social duties. In the last part a fundamental role of the mind and the internal leader-demon was described. According to the thinker nothing is more important than the mind and our actions are entirely under its authority. Mind whereas it is a deity it is the emanation of the universal deity. On that account internal mind must break free from the rule of the sensual impulses and experiences which are merging with the body. In such a way Mark Aurelius applied the Platonic dichotomy to the stoical distinguishing and constructed his own hierarchy of values, using reflections of thinkers preceding him.